Using Vector and Conventional Approach in Calculating Distance in a Three Dimensional Objects - Rahadi, Andi Pujo (Jurnal Padegogik, 2019)
Many of high school students find difficulty in studying three dimensional geometry. They find difficulty in understanding three dimension objects such as cube, cuboid, pyramide, etc. Most students fail to make correct perception about the distance to calculate, when the problems are dealing with lines or planes. Only students with good spatial capability can solve such problems. This research focused on making new approaching method to understand and then calculate the distance in a three dimensional objects. The approach is vector approach, including develop connection vectors, normal vector of a plane, and calculating distance from a point to certain line or plane using vector theorems. The Approach was tested by experimental study to a class of XII grade of high school students in SMAN 1 Parongpong, Indonesia, consists of 30 students, and conducted in six meeting. A similar class treated with the conventional spatial approach as the control class. SPSS 20 was used to analyze the research data. Based on the research data analysis, the conclusion of the study was that students treated with vector approach achieve higher performance improvement compare with the students treated with conventional approach. By using vector theorems to solve three dimensional problems, we turn the theory into action. Keywords : Vector Approach, Three Dimensional, Distance, Line, Plane